An Assessment of aluminum contamination in neonatal parenteral nutrition solutions based on measured versus labeled content - Haya I. Aljohar; Rania A. Nawawi; Nora S. Albanyan; Suliman Aljarboa; Razan S. Orfali (Elsevier, 2024)
Aluminum can potentially cause toxicity in pediatrics and neonates receiving parenteral nutrition. Some PN solutions and ingredients in Saudi Arabia do not comply with US FDA regulations regarding aluminum exposure. This study aims to determine the aluminum concentration in samples of PN solutions and ingredients used to feed infants in Saudi Arabia. The aluminum in the samples was determined using inductively coupled plasma mass spectrometry. The concentration of metal contaminants in each sample was determined in triplicate. The aluminum content of 38 samples was investigated, 15 of which originated from components included in the prepared PN solutions. Among the 15 samples, the least measurable aluminum content was detected in potassium chloride solutions (0.81 mcg/L). In contrast, the greatest amount of aluminum was detected in potassium phosphate and calcium gluconate (141,64 mcg/L and 462.7 mcg/L), respectively. The results showed that the final PN solution (PNS) product contained more aluminum levels than the content ingredients; in addition, the study found a statistically significant relationship among 18 pediatric patients at KFMC who had intestinal failure and needed long-term parenteral nutrition. Specifically, their high aluminum levels, exceeding the normal range of 0.6 ng/ml, indicate that the current use of PN solutions will likely cause toxicity due to aluminum contamination in additives. Hence, reducing aluminum in PN solutions is imperative to ensure patient safety.